KEMAMPUAN PESERTA DIDIK TPQ AL-KAUTSAR MEMBACAAL-QUR’AN DI KELURAHAN BATANG BUNGO, PROVINSI JAMBI - Febby Anggraini; Junaidi Junaidi (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is motivated by the low ability to read the Qur'an of students who are taught by cleric Chelsea at TPQ Al-Kautsar such as students who are not fluent in reading the Qur'an, the difficulty of implementing the science of recitation according to applicable rules and, the difficulty recite makhorijul letters. This study aims to determine how the ability to read the Qur'an of students at TPQ Al-Kautsar, Batang Bungo Village, Jambi Province and what factors affect the ability to read the Qur'an of students at TPQ Al-Kautsar, Batang Bungo Village. , Jambi Province. This research is a field research (filed research) using a qualitative descriptive approach. Collecting data through interviews, observation and documentation. To get valid data, the writer conducted interviews with key informants and supporting informants, then the writer analyzed the data using descriptive analytic. The results showed that the ability to read the Qur'an of students at TPQ Al-Kautsar who was taught by Ustadz Chelsea was found. Ten of the fourteen students taught by Ustadz Chelsea already had the ability to read the Koran according to the rules. What applies, the rest there are still those who do not have fluency in reading the Qur'an, there are those who have memorized the knowledge of recitation given by the ustadzah but still have difficulties in implementing it and there are also those who still have difficulty in reciting certain letters. Factors that affect the ability to read the Qur'an of students who are taught by cleric Chelsea at TPQ Al-Kautsar are caused by several factors, including physiological factors or physical health factors, psychological factors such as student intelligence and student interests and motivations, social environmental factors of students, factors of facilities and infrastructure that support learning activities and learning methods used by educators that are adjusted to the circumstances of students. Keyword: Ability to Read Al-Qur'an